ANALISIS MINAT SISWA TERHADAP EKSTRAKURIKULER PENCAK SILAT DI SMP N 37 SEMARANG - Madia Nur Alisa; Bertika Kusuma P; Muh Isna Nurdin W; Suprapti (JURNAL ILMIAH PENJAS (Penelitian, Pendidikan dan Pengajaran), 2024)
This research aims to determine significantly the size of the extracurricular interest in pencak silat at SMPN 37 Semarang. Interest is applied as interest or liking or activity without compulsion. Extracurricular administrators from the school manage everything that is useful for achieving non-academic achievement goals. This research uses a quantitative descriptive approach with a survey method that uses data collection techniques, namely by using questionnaires. The sample size consisted of 388 students attending SMPN 37 Semarang. This interest research uses an overall sampling technique. The results of the research show that students' interest in taking part in extracurricular pencak silat at SMPN 37 Semarang is relatively low. It can be seen that 16 students (4.12%) showed very high interest, 168 students (43.30%) showed high interest, 198 students (51.03%) showed low interest and 6 students (1.55%) %) indicates very low interest. This shows that students at SMPN 37 Semarang have low interest, namely 51.03%, in playing pencak silat.